Investigating Non-LTE Abundances of Neodymium in Metal-poor FGK Stars - Dixon, John D.; Ezzeddine, Rana; Li, Yangyang; Merle, Thibault; Bautista, Manuel; Guo, Yanjun (The Astrophysical journal, 2025)
The dominant site(s) of the r-process are a subject of current debate. Ejecta from r-process-enrichment events like kilonovae are difficult to directly measure, so we must instead probe abundances in metal-poor stars to constrain r-process models. This requires state-of-the-art non-LTE (NLTE) modeling, as LTE is a poor approximation for the low-opacity atmospheres of metal-poor giants. Neodymium (Nd) is a prominent r-process element detected in both near-infrared kilonova spectra and the spectra of metal-poor stars, so precise Nd stellar abundances are particularly needed to model kilonovae and constrain r-process sites. We thus constructed an Nd i/Nd ii model atom to compute NLTE abundances in FGK metal-poor stars. We obtain A(Nd)⊙ = 1.44 ± 0.05, in agreement with the meteoritic value, when calibrating the model atom with a Drawin hydrogen collision factor of SH = 0.1. For a sample of metal-poor r-process-enhanced stars with observed optical and near-infrared Nd ii lines, we find NLTE Nd corrections in the range −0.3 to 0.3 dex. Optical and UV lines have positive NLTE corrections, whereas H-band lines have negative corrections. Additionally, we compute a large grid of NLTE corrections for 122 Nd ii spectral lines ranging from the UV to the H band, for stellar parameters of typical metal-poor FGK dwarfs and giants with −3 ≤ [Fe/H] ≤ −1 and −2 ≤ A(Nd) ≤ 2. Within this grid, we find NLTE corrections ranging from −0.3 to +0.5 dex. Deviations from LTE are found to be strongest for blue lines with low excitation potentials in the most metal-poor giants.